Initial Severity of Schizophrenia and Efficacy of Antipsychotics: Participant-Level Meta-analysis of 6 Placebo-Controlled Studies. - Furukawa, T; Levine, S; Tanaka, S; Goldberg, Y; Samara, M; Davis, J; Cipriani, A; Leucht, S (American Medical Association, 2015)
IMPORTANCE: Antipsychotic drugs constitute the mainstay in the treatment of schizophrenia, and their efficacy is well established in hundreds of randomized clinical trials. However, it is not known whether they are effective or how effective they are across the wide range of baseline symptom severity. OBJECTIVE: To examine the influence of baseline severity of schizophrenia on the efficacy of antipsychotic drugs. DESIGN, SETTING, AND PARTICIPANTS: Meta-analysis of participant-level data from 3 pivotal randomized trials of acute schizophrenia (n = 611) and 3 pivotal trials in patients with predominantly negative symptoms of schizophrenia (n = 475). INTERVENTIONS: Olanzapine or risperidone vs placebo, and amisulpride vs placebo. MAIN OUTCOMES AND MEASURES: Change scores on the Positive and Negative Syndrome Scale (PANSS; score range, 30-210) and the Scale for the Assessment of Negative Symptoms (SANS; score range, 0-125) up to 6 weeks after baseline. The relationship between baseline and change scores for the drug and placebo groups was examined with 8 competing mixed-effects models for repeated measures. RESULTS: The best-fitting models showed that, for both types of patients, the interactions between baseline symptom severity and treatment were statistically significant (P < .01). The greater the baseline severity was, the greater the magnitude of the differences was between active treatment and placebo. In acute treatment, the mean differences in PANSS change scores were 9.5 points for patients who were mildly ill at baseline (baseline PANSS score of 58), 13.7 for moderately ill patients (baseline PANSS score of 75), 18.8 for markedly ill patients (baseline PANSS score of 95), and 24.0 for severely ill patients (baseline PANSS score of 116). In treatment of predominantly negative symptoms, the mean differences in SANS change scores were 1.7 for those who were moderately ill (baseline SANS score of 55), 5.7 for markedly ill patients (baseline SANS score of 70), and 9.7 for severely ill patients (baseline SANS score of 85). CONCLUSIONS AND RELEVANCE: We can expect benefits of antipsychotic drugs for the full spectrum of patients likely to be treated for acute schizophrenia and for highly symptomatic patients with predominantly negative symptoms. Toward the mildest end of the spectrum, clinicians need to be aware that patients benefit less in terms of symptom improvement but may experience full adverse effects of antipsychotics. Clinicians also need to be aware that in addition to the treatment of active symptoms, which was the focus of this study, antipsychotics have another important action, namely to prevent relapses among patients in remission.